RHYTHM AND CULTURAL INTERSECTIONS IN AREIA II, BY ALEXANDRE LUNSQUI: INFLUENCES IN HIS COMPOSITIONAL PROCESS (Orfeu, 2020)
This article intends to analyze rhythmic aspects in Areia II, by composer Alexandre Lunsqui. Whether they come from the classical repertoire, or from musical manifestations external to this repertoire, such as ethnic music, we analyze the different rhythmic influences occurringthroughout the composition. The article maps out the rhythmic figures used in the work in relation to the creative strategies employed by the composer.
Keywords: Rhythm; contemporary music; traditional African music; composition